2004
DOI: 10.1590/s0100-46702004000100009
|View full text |Cite
|
Sign up to set email alerts
|

Thermoanalytical study of purine derivatives compounds

Abstract: Thermal methods of analysis are now used in a very large range of scientific investigations. In this work simultaneous thermogravimetry-differential thermal analysis (TG-DTA), X-Ray powder diffractometry and infrared spectroscopy were used to study the derivative compounds of purine, i. e. aminophylline, theophylline, caffeine and uric acid. The results led to informations about the thermal stability and thermal decomposition of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
4
16
0
Order By: Relevance
“…The relatively small amount of theophylline (13%) in the PM and nanofibers may explain why the melting of theophylline is not recognized in the DSC thermograms of PM or nanofibers, but it cannot account for the lack of thermic events during the cooling phase or in the second heating of pure theophylline. Crystallization of theophylline during the DSC cooling phase has been reported previously [13,16].…”
Section: Resultsmentioning
confidence: 86%
“…The relatively small amount of theophylline (13%) in the PM and nanofibers may explain why the melting of theophylline is not recognized in the DSC thermograms of PM or nanofibers, but it cannot account for the lack of thermic events during the cooling phase or in the second heating of pure theophylline. Crystallization of theophylline during the DSC cooling phase has been reported previously [13,16].…”
Section: Resultsmentioning
confidence: 86%
“…The FT‐IR spectra from all samples and controls were evaluated but, as the different T inlet considered did not produce products with different spectra, only the spectra of the spray‐dried milk powders atomized at 105 °C are presented as an example (Figure ). Theophylline (raw material) showed bands at 3120.96 cm −1 (N–H stretching), at 1716.72 cm −1 and 1668.50 cm −1 (C=O stretching, amide I), at 1566.27 cm −1 (N–H bending, amide II) and the N–H wagging at 742.63 cm −1 . For the samples with milk, regardless the fat content, it was possible to identify bands at 3468.16–3304.20 cm −1 (O–H and N–H stretching in the protein structure), at 1660.78–1643.42 cm −1 and 1546.98–1545.05 cm −1 (amides I and II, respectively, in the proteins’ structure) and in the region of 1200–900 cm −1 , corresponding to the so‐called saccharide bands.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, Schneitzler et al [22] have reported TGA of purine derivatives such as aminophylline, theoophylline, caffeine and uric acid. It was found that uric acid was stable up to 375°C and thereafter the mass loss occurred through rapid process.…”
Section: Discussionmentioning
confidence: 99%